General Guidelines for the Use of Colour on Electronic Charts - Kaufmann, Roy; Glavin, Stephen J. (The International Hydrographic Review, 2015)
An Electronic Chart Testbed has been developed by the Canadian Hydrographic Service for the purposes of investigating design and safety aspects of using electronic charts as a navigational aid for mariners. The proper selection and specification of colour is a fundamental aspect of effective display design. This report outlines the issues involved in the use of colour on displays as they relate to the Electronic Chart Display and Information System (ECDIS). Topics include luminance, high and low ambient illumination, brigthness, display background, colour selection, information clutter, colour coding convention, stimulus size, image location, visual effects, and user characteristics. Since ECDIS is relatively young in its development, the purpose of the review is to provide some general guidelines for selecting and using colours on electronic charts.